Strengthening leadership through networking: a mixed method evaluation of a core component of the Emerging African Leaders Programme (EALP) - Muneesamy, Loganaden (Division of General Surgery, 2021)
In line with its mission to promote public leadership in Africa, the UCT Nelson Mandela School of Public Governance (NMSPG) implements the Emerging African Leaders Programme (EALP). With the use of an intensive two-week residential workshop in Cape Town, integral coaching and an EALP alumni network, the programme endeavours to enhance the leadership capacity of emerging African leaders. The purpose of the EALP alumni network is to keep EALP alumni connected, enable them to have an ongoing dialogue and facilitate collaborations with the ultimate objective of making a contribution to addressing Africa's wicked challenges. A mixed method formative outcome evaluation of the networking component of the EALP was conducted. Data was collected by means of a document review, an online survey, semi-structured interviews and focus group discussions involving the main stakeholders. The findings showed that the EALP alumni network had created, albeit in a suboptimal resource-constrained context, positive outcomes at individual, network, organisational and policy-making levels. The network helped to increase the self-confidence, connectivity, networking ability, networking, problem-solving and decision making capacity, learning, social capital and career prospects of EALP alumni. Furthermore, most of the EALP alumni expressed above average trust and commitment in the EALP alumni network, and, opined that efforts were made to ensure effective inclusion of all network members. On the other hand, on average, EALP alumni, were generally connected and interacted with others within their respective cohort, with mutual support and exchange of information and other resources only occasionally taking place among them. Of the sample, fifty percent of the EALP alumni experienced network cohesion. On average, EALP alumni, reported that it was easy to collaborate on the network but they had developed few productive collaborations with others. Slightly more than half of EALP alumni were satisfied with the management of the EALP alumni network and one fifth of them had fully internalised the network goal. Some positive outcomes were also noted at organisational and policy-making levels. With a view to strengthening the EALP alumni network, ensuring its sustainability and improving its effectiveness, the following recommendations have been made: formulation of a strategy and plans for the network, introduction of a monitoring, evaluation and learning system, formalisation of the network, appointment of a dedicated network manager to engage and support EALP alumni, and ongoing capacity-building.